Demographic and Clinical Profile of COVID-19 and Post-COVID Complications in Children at a Specialized COVID Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Clinical manifestations of children with COVID 19 differ widely from adult cases. They usually have milder disease. There are limited data on pediatric COVID patient from Bangladesh. This study was conducted to find out the demographic and clinical characteristics of COVID-19 in children and post-COVID complications in a specialized COVID hospital from south-east part of Bangladesh.Materials and methods: This retrospective study was conducted in Bangladesh Institute of Tropical and Infectious Diseases (BITID), Fouzderhat, Chattogram from April 2020 to September, 2020. Medical records of PCR-confirmed pediatric COVID- 19 cases were collected. Data regarding age, sex, residence, contact history, presenting features, hospitalization, comorbidities and post-COVID complication were noted. Statistical analysis was done by SPSS 20.0 version.Results: Out of total 2058 pediatric patients, 183 (8.9%) were PCR confirmed COVID- 19 cases. Male to female ratio was 1.3:1 and median age was 11 years (Age range 3 months to 17 years). 35% patients belonged to the age group 11 to 15 years. Family clustering was the main transmission route (81.3%) and parents were the most common source (77.8%). Most of the patients lived in the Chattogram metropolitan area (57.1%). Highest peak of infection were during the month of May and June. Many of them (38.9%) were asymptomatic. Among them 11-15 years age group were mostly asymptomatic (38.6%). Most common presentation was fever (85%) followed by cough (37.5%), runny nose (25%) and sore throat (19.3%). For 2-5 years age group, gastrointestinal symptoms were predominant (30%). Only 9 patients (6.3%) required hospitalization. The median time from onset to cure was 3 days (Ranging from 1 to 30 days). Total 8 patients (5.6%) developed post-covid complications. Those were extreme weakness (2.8%), anorexia (2.1%), chronic cough (1.4%), insomnia (0.7%) and headache (0.7%). 16-17 years patients mostly suffered from these complications. There was no mortality in this pool of pediatric patients.Conclusion: COVID 19 in pediatric patients is distinct from adults. There was slight male preponderance with 11-15 years age group being more susceptible. Most common source of infection were parents. Many patients had asymptomatic infection. Fever was the most common presenting feature followed by respiratory symptoms. Very few patients developed post-COVID complications which were mild and there was no mortality.Chatt Maa Shi Hosp Med Coll J; Vol.21 (1); January 2022; Page 61-65